GAMBARAN GAYA KEPEMIMPINAN KEPALA RUANGAN PERAWATAN DI RUMAH SAKIT PKU MUHAMMADIYAH YOGYAKARTA - Rahadian Syah, Deby Zulkarnain (Universitas Jenderal Achmad Yani Yogyakarta, 2015)
Background: PKU Muhammadiyah Hospitalof Yogyakarta is an Islamic type B referral hospital in Special Regency ofYogyakarta and Central Java. Inspite of being a referral hospital, an improvement in services and nursing care still needs to be considered. Head of nursing section has a significant role in organizing theassociate nurses in effort todeliveringbetter services. A successful head of nursing section must be a good identifier and could appreciate the spirit of enquiry. Methods: This research was a quantitative-descriptive research. Measurement tool of this research was a questionaire that were distributed to 94 respondents. The subjects of this research werevocational nurses atinpatient room of PKU Muhammdiyah Hospital of Yogyakarta. Results:This research showed that the leadership styles assessed by the associate nurses in Ibnu Shina wardwas consulting style (72,7%), Marwah wardwas consulting style (56,3%), Roudhoh wardwas consulting style (63,3%), Arafah wardwas participating style (53,8%), Shofa-musdalifah wardwas consulting style (71,4%), Zam-zam wardwas participating style (81,8%), and Multazam wardwas consulting style (72,2%). Conclusion:The situational leadership style applie by the head of nursing section was dominantly consulting leadership style. Keywords: Leadership, head of nursing section